Comprehensive review of nonisolated bridgeless power factor converter topologies - Ankit Kumar Singh; Anjanee Kumar Mishra; Krishna Kumar Gupta; Taehyung Kim (IET Circuits, Devices and Systems)
Abstract The intention of this study is to provide a critical review of single‐phase nonisolated bridgeless power factor converter topologies, which will be useful for novice researchers in the power electronics field. The bridgeless nature of the converter reduces the number of switching devices in the current path and achieves higher efficiency. Nonisolated topologies are considered in this review due to the inherent advantages they offer such as lower cost, weight and size and higher efficiency, which are desirable for systems such as on‐board electric vehicle battery chargers, direct current power supplies and variable speed drives. These topologies are derived from conventional boost, buck and buck/boost converters. Moreover, the topologies can be operated in continuous or discontinuous conduction modes subject to their applications. Each topology is described in terms of its advantages and limitations. In addition, a comparative study is conducted for each group (boost, buck and buck/boost).